Impacts of free trade agreements on business activity in Asia: The case of Japan - Daisuke Hirastuka; Hitoshi Sato; Ikumo Isono (Asian Development Bank Institute (ADBI), 2009)
Free trade agreements (FTAs) have proliferated in East Asia in recent years. As of December 2008, eight bilateral FTAs and one plurilateral FTA involving Japan have entered into force; additional negotiations are ongoing with several more countries. The proliferation of FTAs in Japan and other Asian countries is thought to be behind the perceived overlapping rules of origin (ROO) problem, or spaghetti bowl effect. Effective implementation of FTAs is becoming an increasingly pressing issue for Japanese firms because Japanese firms have expanded overseas, particularly into the rest of Asia, which has contributed to the formation of production networks in East Asia. There have been numerous ex ante studies on the impacts of FTAs in which they assumed that any firm can maximize profits by utilizing FTA preferential tariffs without any additional costs. In reality, however, FTAs require certificates of origin, which impose additional administrative costs on firms. It is doubtful whether firms really use FTAs because FTAs are not compulsory. With this in mind, this study investigates how East Asian FTAs have affected the behavior of Japanese firms, including their affiliates operating overseas. Our study concluded that presently FTAs are neither well known nor well utilized by Japanese firms. There are several reasons for low utilization. Firms either do not fully understand or are not knowledgeable about the existing FTAs. There are some trade arrangements from which tariffs are completely exempted, such as the Information Technology Agreement and the special exemption of tariffs under Thailand's Board of Investment laws. Phase-out tariff reduction schedules, in which tariffs are gradually reduced over several years, discourage FTA use. Furthermore, the administration to prepare documents for certificates of origin is cumbersome. As a result, in general, small- and medium-sized enterprises cannot use FTAs, meaning that they are penalized in utilizing FTAs. Only a few FTAs with large economic partners are utilized by Japanese firms. Bilateral FTAs are not more beneficial than plurilateral FTAs, in particular in East Asia where production networks have developed.
Keywords: F13; F14; N75; 330